Embalagens multicamadas: fundamentos e aplicações - Miler, Matheus (Universidade Federal de São Carlos, 2023)
Multilayer packaging consists of structures composed of multiple layers of materials, which can be similar or different, such as aluminum, plastic, and paper. These packages play a crucial role in protecting products and food, ensuring their integrity and extending their shelf life. However, the use of multilayer packaging also presents significant challenges, especially from an environmental perspective, due to post-consumer disposal issues. An example of the advantage of multilayer packaging is its ability to provide effective barriers against external factors such as moisture, light, and oxygen, which can degrade packaged products. This contributes to preserving product quality and reducing waste. However, disadvantages include the complexity of their composition, making recycling and proper disposal more difficult, thereby increasing environmental impacts. The environmental concerns associated with multilayer packaging have raised growing concerns, leading to the search formsustainable solutions. Brazil, a country recognized for its sustainable practices, is addressing this challenge as an improvement opportunity, given the significant amount of multilayer packaging consumed annually in the country. Measures such as promoting recycling and seeking more environmentally friendly packaging alternatives are among the ongoing initiatives. In summary, multilayer packaging plays an important role in product protection but also presents environmental challenges. The literature review emphasizes the need to address these challenges for sustainability in packaging production and consumption
Multilayer packaging: fundamentals and applications
Keywords: Embalagem multicamadas; Reciclagem; Sustentabilidade; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS